2024
DOI: 10.3390/medicina60020315
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Supplemental Ultrasound-Guided Pericapsular Nerve Group (PENG) Block Combined with Lateral Femoral Cutaneous Nerve Block in Patients Receiving Local Infiltration Analgesia after Hip Fracture Surgery: A Prospective Randomized Controlled Trial

Seung-hee Yoo,
Min-jin Lee,
Min-hyouk Beak
et al.

Abstract: Background and Objectives: Local infiltration analgesia (LIA) represents a potential approach to reducing pain in patients undergoing total hip arthroplasty (THA). The pericapsular nerve group (PENG) block also provides adequate analgesia for fractures and THA. As most hip surgeries use a lateral incision, affecting the cutaneous supply by branches of the lateral femoral cutaneous nerve (LFCN), the LFCN block can contribute to postoperative analgesia. However, no studies have investigated the effectiveness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…One RCT from South Korea in 2024 placed patients into two groups, one receiving local infiltration by the surgeon (LIA) and the other with LIA + PENG and LFCN. This study showed significant reductions in pain scores and opioid consumption [ 20 ]. Another study combining PENG and LFCN evaluated whether this combination could be used as a primary block in patients.…”
Section: Peripheral Nerve Blocksmentioning
confidence: 99%
“…One RCT from South Korea in 2024 placed patients into two groups, one receiving local infiltration by the surgeon (LIA) and the other with LIA + PENG and LFCN. This study showed significant reductions in pain scores and opioid consumption [ 20 ]. Another study combining PENG and LFCN evaluated whether this combination could be used as a primary block in patients.…”
Section: Peripheral Nerve Blocksmentioning
confidence: 99%